Discounted Cash Flow Method in Assessing the Value of the Enterprise - A., Askarova Zh. (Farabi Journal of Social Sciences, 2019)
Abstract. Evaluation of the rights of the owners of the company, is the primary indicator of the company’s profit potential over time. The income approach as the basic principle. Method of discounting future revenues, as the present value of the future income from the acquisition of objects, successfully used for the assessment of real estate. The benefits of real estate transactions in the future, future revenues and reversïyanı time in the form of income during the period of ownership, ie the profit from the sale of the property at the end of the period of ownership. The enterprise value – the amount of income for several years and calculated as the difference between the amount of the borrowed funds which are involved, generates future income, expenses and cash flows. Future costs and the results of the evaluation of the company are to be determined within the reporting period and the amortization horizons. Computer horizons are measured by the number of steps of the calculation. Discounted cash flow method, the assets of the enterprise value of their cash income are measured by the ability to import.